Beauty: a bioform of storytelling? (ENTHYMEMA, 2018)
According to twentieth-century experimental psychology, beauty consisted mainly in the recognition of a host of prototypical forms, so perceiving something average and generic aroused a sense of reassuring familiarity. The recent discovery of the principles of Darwinism, above all by neuro-scientists and bio-neurologists, on the other hand, suggested the opposite, namely that beauty is a form of evolutionary fitness: a sort of storytelling used firstly in the animal kingdom, then by mankind up to the Late Stone Age, in which males tried to persuade a female to mate. The recent theory of the so-called ‘period-eye’ has shown the constant influence of our surroundings on our perception of what is beautiful, confirming the neo-Darwin theories, in the light of historical and social mechanisms, not only bio-evolutionary.
Keywords: beauty; aesthetic perception; prototypicality; evolutionary fitness; period-eye; rewarding system; peak shift; storytelling